Does routine child health surveillance contribute to the early detection of children with pervasive developmental disorders? – An epidemiological study in Kent, U.K. - Ritchie Jane (BMC Pediatrics, 2004)
Abstract Background Recently changed guidelines for child health surveillance in the United Kingdom (U.K.) suggest targeted checks only, instead of the previously conducted routine or universal screening at 2 years and 3.5 years. There are concerns that these changes could lead to a delay in the detection of children with autism and other pervasive developmental disorders (PDD). Recent U.K. studies have suggested that the prevalence of PDD is much higher than previously estimated. This study establishes to which extent the routine checks contributed to the early detection and assessment of cases of PDD. Simultaneously we have evaluated the process involved and estimate the prevalence of PDD in our district. Methods Retrospective study design utilising community medical files. Headteachers of schools (n = 75) within Maidstone district (Kent) were asked to report all children with an established diagnosis of autism or PDD attending year 4 (born '91 and '92 / n = 2536) in October 2000 based on educational records. Results 59 schools (78.7%) took part in the study. A total of 33 children were reported. 21 fulfilled the inclusion criteria (12 falsely reported). The prevalences were (per 10,000): PDD 82.8 (male to female ratio 6:1), childhood autism 23.7, Asperger's syndrome 11.8 and autistic spectrum disorder 47.3. Co-existing medical conditions were noted in 14.3%; 52.4% were attending mainstream schools. In 63.2% of cases concerns – mainly in the area of speech and language development (SLD) – had been documented at the 2 year check. At the 3.5 year check concerns were noted in 94.1% – the main area was again SLD (76.5%), although behavioural abnormalities were becoming more frequent (47.1%). A total of 13 children (68.4%) were referred for further assessment as a direct result of the checks. Conclusions The prevalences for different types of PDD were similar to figures published recently, but much higher than reported a few years ago. Analysis of our data suggests that routine surveillance is a valuable contributing factor for the early detection of PDD and thereby facilitates early intervention. Thus, if routine surveillance ceases, then an alternative method of early detection should be put in place.